Watch, Imagine, Attempt: Motor Cortex Single-Unit Activity Reveals Context-Dependent Movement Encoding in Humans With Tetraplegia - Vargas-Irwin, Carlos E.; Feldman, Jessica M.; King, Brandon; Simeral, John D.; Sorice, Brittany L.; Oakley, Erin M.; Cash, Sydney S.; Eskandar, Emad N.; Friehs, Gerhard M.; Hochberg, Leigh R.; Donoghue, John P. (Frontiers in Human Neuroscience, 2018)
Planning and performing volitional movement engages widespread networks in the human brain, with motor cortex considered critical to the performance of skilled limb actions. Motor cortex is also engaged when actions are observed or imagined, but the manner in which ensembles of neurons represent these volitional states is unknown. Here we provide direct demonstration that observing, imagining or attempting action activates shared neural ensembles in human motor cortex. Two individuals with tetraplegia (due to brainstem stroke or ALS) were verbally instructed to watch, imagine, or attempt reaching actions displayed on a computer screen. Neural activity in the precentral gyrus incorporated information about both cognitive state and movement kinematics; the three conditions presented overlapping but unique, statistically distinct activity patterns. These findings demonstrate that individual neurons in human motor cortex reflect information related to sensory inputs and volitional state in addition to movement features, and are a key part of a broader network linking perception and cognition to action.